MODEL PELAYANAN PEKERJA SOSIAL TERHADAP KORBAN BENCANA BANJIR DI KOTA BANJAR PROVINSI KALIMANTAN SELATAN TAHUN 2021 - Pajrin Prihartini; Mutia Aini; Nurhikmatu Sya’diah; Radhina Fasya Tazkianida (Jurnal Manajemen Bencana (JMB), 2021)
Banjar is one of the cities in South Kalimantan Province which on January 9, 2021 was affected by floods. Many people became victims of the disaster. This causes the community to be stressed and traumatized after the disaster. Social intervention is urgently needed to assist recovery and reduce the level of trauma to communities who are victims of disasters. The role of a social worker to carry out social services is very important, because the knowledge of a professional social worker in carrying out practices and services for victims is not only related to the underlying theory, but also to the knowledge and skills to learn the attitudes and habits that are unique to disaster victims. Each victim has a different background and story, so the service model provided by social workers is also different. Through this paper, the author wants to explore what service models and what services are provided and implemented by social workers in social work practices for flood victims in Banjar City, South Kalimantan Province. The research uses a qualitative method with a literature study approach.